Comparative study of surgically induced astigmatism in superior versus temporal incision in small incision cataract surgery cases - Kavitha, Kuruva Nandyala Sree; Kishore, Arikeri Krishna; Reddy, Ganta Sudhakar; Jehan, Khaiser (International Journal of Research in Medical Sciences, 2017)
Background: Location of incision has a significant impact on surgical outcome. It has been reported that temporal incisions induce less astigmatism than superior incisions indicating the importance of incision location. The objective of the present study was to study the effect of surgical induced astigmatism in superior versus temporal incision in small incision cataract surgery cases. Methods: 100 patients of cataract attending to Sarojini Devi eye hospital with the rule and against the rule astigmatism were included in the study. The astigmatic profile and the effect of surgical incision on astigmatism were studied. A prospective study was done in which patients were divided into two groups. MSICS was performed with superiorly located incision in group I and temporally located incision in group II. Results: Out of the total 100 patients undergoing MSICS, 59 patients had ATR, 36 patients had WTR and 5 patients had no astigmatism. Thus the pre-operative astigmatic profile shows that ATR is more common type of astigmatism in this group. Among 50 patients in superior incision group, 18 had pre-operative WTR, 29 had ATR and 3 did not have astigmatism. Postoperatively the no. of patients with WTR decreased to 10, the no. of patients with ATR increased to 35 showing that superior incision flattens vertical meridian and steepens the horizontal meridian causing ATR shift. Among 50 patients in temporal incision group, 18 had pre-operative WTR, 30 had ATR and 2 did not have astigmatism. Post operatively the no of patients with WTR increased to 25, the no of patients with ATR decreased to 20. Conclusions: Placement of incision on steep axis reduces pre-existing astigmatism. Thus in ATR astigmatism it is placed temporally and in WTR astigmatism it is placed superiorly. Thus a simple modification in incision placement can minimize surgically induced astigmatism and reduce pre-existing astigmatism